Unveiling the complexity of neurofibromatosis type 1: Innovations in genetic understanding and clinical management. A narrative review - Jurca, Aurora; Pop, Simona; Jurca, Claudia Maria; Vesa, Cosmin Mihai; Jurca, Alexandru Daniel (Biomedical papers, 2025)
Neurofibromatosis type 1 (NF1) is an autosomal dominant disorder caused by mutations in the NF1 gene. The most important signs are cafe-au-lait spots, intertriginous freckling, and neurofibromas. The disease has a progressive course, the penetrance is almost complete, and reduces life expectancy by approximately 15%. This review examines the current literature, including NIH (National Institute of Health) diagnostic criteria, genetic testing, genotype-phenotype correlations, and emerging therapies. Genetic testing has improved diagnostic accuracy, particularly for age-dependent clinical features. The genotype-phenotype correlation in NF1 underscores that specific genetic alterations, such as large deletions in the NF1 gene, are frequently linked to more severe clinical outcomes. These deletions often result in early onset of symptoms, a higher frequency of tumor development, and increased tumor burden, all of which contribute to a more complex clinical course. Consequently, individuals with these genetic changes require intensive and continuous monitoring to manage potential complications and prevent further health deterioration. Advances in therapies such as MEK inhibitors offer hope for inoperable plexiform neurofibromas, while surgery remains the primary option for localized tumors, despite the risk of recurrence. Multidisciplinary care and genetic advancements are crucial for improving the prognosis and quality of life of patients with NF1.
Keywords: neurofibromatosis type 1; NF1 gene; genotype-phenotype correlation; MEK inhibitors